Comparison of cervical colposcopic findings with Pap smear of colposcopiy candidates referred to Amiralmomenin Hospital in 2016-2018 - Mahas Daei-Sarraf; Hoda Doustmohammadi; Mojgan Rahmanian (Mashhad University of Medical Sciences, 2022)
Introduction: Cervical cancer is one of the most common causes of cancer death in women. The present study was performed aimed to evaluate and compare Pap smear and colposcopy findings as cervical cancer screening methods in patients reffered to Amir Al-Momenin hospital of Semnan.Methods: In this cross-sectional and retrospective study, liquid-based Pap smear and colposcopy results of 200 colposcopiy candidates referred to the clinic of Amir Al-Momenin Hospital were studied in 2016-2018. In this study, all patients who had undergone colposcopy for various reasons and also had done Pap smear were examined. The data of each patient were recorded in a researcher-designed checklist. The checklist consisted of demographic and main data sections. The abnormalities in Pap smears included pre-invasive and invasive positive cervical lesions. The abnormalities in colposcopy included pre-invasive and invasive positive cervical lesions. Data were analyzed by SPSS (version 23) and independent t-test, chi-square, or Fisher's test. P<0.05 was considered statistically significant.Results: From 200 patients, 40 cases (20%) showed positive Pap smear. Also, colposcopy results showed that 17 patients (8.5%) had positive findings. There were signficant differences in the frequency of positive and negative results of Pap smear and colposcopy in patients with symptoms of post coital bleeding (P=0.021), intermenstrual bleeding between periods (P=0.035), vaginal discharge (P=0.009), and pelvic pain (P = 0.011). Conclusion: The non-positive results of Pap smear in positive cases of colposcopy emphasizes the quality control of Pap smear procedures and indicates the need to use colposcopy in suspicious cases. Direct colposcopy is recommended in case of warning signs such as post coital bleeding and abnormal discharge.